A 25-Year Retrospective of Health IT Infrastructure Building: The Example of the Catalonia Region - Jordi Piera-Jiménez; Gerard Carot-Sans; Marina Ramiro-Pareta; Maria Mercedes Nogueras; Júlia Folguera-Profitós; Pepi Ródenas; Alba Jiménez-Rueda; Thais de Pando Navarro; Josep Antoni Mira Palacios; Joan Carles Fajardo; Joan Ustrell Campillo; Emili Vela; et al. (Journal of Medical Internet Research)
Over the past decades, health care systems have significantly evolved due to aging populations, chronic diseases, and higher-quality care expectations. Concurrently with the added health care needs, information and communications technology advancements have transformed health care delivery. Technologies such as telemedicine, electronic health records, and mobile health apps promise enhanced accessibility, efficiency, and patient outcomes, leading to more personalized, data-driven care. However, organizational, political, and cultural barriers and the fragmented approach to health information management are challenging the integration of these technologies to effectively support health care delivery. This fragmentation collides with the need for integrated care pathways that focus on holistic health and wellness. Catalonia (northeast Spain), a region of 8 million people with universal health care coverage and a single public health insurer but highly heterogeneous health care service providers, has experienced outstanding digitalization and integration of health information over the past 25 years, when the first transition from paper to digital support occurred. This Viewpoint describes the implementation of health ITs at a system level, discusses the hits and misses encountered in this journey, and frames this regional implementation within the global context. We present the architectures and use trends of the health information platforms over time. This provides insightful information that can be used by other systems worldwide in the never-ending transformation of health care structure and services.